Two new species and new records of chiggers (Acari: Leeuwenhoekiidae, Trombiculidae) from birds in Vietnam - Kaluz, Stanislav K.; Hung, Nguyen Manh; Capek, Miroslav; Literak, Ivan (Zootaxa, 2016)
A total of 12 chigger species (Acariformes: Trombiculidae) occurred on 7 bird species in Vietnam. Two new species, namely Neoschoengastia vietnamensis sp. nov. and Hypogastia stekolnikovi sp. nov. are described, figured and compared with similar species placed in relevant genera using differential diagnoses of related species. Figures and diagnosis of Leptotrombidium taiyuanense Tian and Wen, 1984 are added. Odontacarus audy (Radford, 1946), Leptotrombidium allosetum Wang, Liao and Lin, 1981, L. taiyuanense, Leptotrombidium hanseni Traub and Lakshana, 1966, Leptotrombidium kunshui Wen and Xiang, 1984, Leptotrombidium paradux Vercammen-Grandjean and Langston, 1976, Leptotrombidium turdicola Vercammen-Grandjean and Langston, 1976, Neotrombicula elegans Schluger, 1966 and Neoschoengastia longitar-salis Schluger and Belskaya, 1966 were recorded in Vietnam for the first time.